An introduction to the phenomenology of religion - Cox, James L. (Continuum, 2010)
Preface -- Defining religion -- Historical background -- Philosophical phenomenology and the social sciences -- Stages in the phenomenological method -- The phenomenological method : a case study -- Myths and rituals -- Religious practitioners and art -- Scripture and morality -- The special case of belief -- The place of the phenomenology of religion in the current and future academic study of religion